Finite-time prescribed performance control for dynamic positioning of pneumatic servo system - Mohd Iskandar Putra, Azahar; Addie Irawan, Hashim; Mohd Syakirin, Ramli (IEEE, 2020)
In this paper, a new prescribed performance function (PPF) with a finite time feature is introduced and integrated as a transformation of the output error for the position control on the pneumatic servo system. The error transformation with a new PPF is formulated named as the finite time prescribed performance control (FTPPC) is attached with PID control that is used for servo pneumatic rod-piston positioning. The pneumatic proportional valve with a double-acting cylinder (PPVDC) system model plant is used as a targeted plant for simulation and comparison study with the conventional PID controller. The improved performance and efficiency of the proposed FTPPC with PID approach is simulated and analyzed by using three different types of input trajectory that include the step input, sinusoidal input dynamic ramp input trajectory as well as the addition of payload as external disturbances. The results show that the proposed FTPPC is capable of improving the nominal controller, such as PID in reducing a steady-state error with a fast settling time as well as low overshoot as compared to the traditional PID controller.